TRADISI SELAKARAN SEBAGAI RITUAL HAJI DI DESA KEMBANG KERANG DAYA NUSA TENGGARA BARAT - Siti Maryam (QOF, 2020)
This research is a qualitative descriptive study that discussed the tradition of selakar as a hajj ritual in the village of Kembang Kerang Daya, West Nusa Tenggara. This research was a field research. The approach used in this research was phenomenology. The data sources in this study were obtained directly from religious leaders, traditional leaders, the Kembang Kerang Daya village community and various literatures. Data collection methods used were observation, interviews, and data analysis. The focus of this research was to know how the implementation of selakaran activities as a pilgrimage ritual in the village of Kembang Kerang Daya, what factors influence the continuity of this tradition and how the selakar tradition influences people's religious behavior. From this research it was found that selakar as a hajj ritual is something that must be carried out by people who are going to perform Hajj. This religious practice is included in the phenomenon of the living Qur'anHadith which is based on the QS. Al-Ahzab: 56 and traditions about the commands and obligations of praying as a form of love for the Prophet. By carrying out the tradition of selakar, namely reading sholawat, dzikir and do’a, according to them it will be reassuring, bring blessings in life and it is believed that it will also benefit people who are performing Hajj, such as safe traveling, staying healthy, enthusiastic in carrying out worship and get the hajj done. In addition, there is an important meaning from the existence of this tradition, namely the practice of spiritual worship that cannot be eliminated in people's lives.